“Jacob’s Blessing” (Gen 49:1–28) in Targumic Interpretation - Kuśmirek, Anna (Collectanea Theologica, 2021)
Genesis 49 shows the scene that takes place at the deathbed of the patriarch Jacob. In the face of his upcoming death, Jacob calls on all of his sons that they may listen to and accept his words of valediction. The patriarch addresses each of them individually. This piece of text serves an example of the biblical poetry in which metaphors play an important role. In the Hebrew text there are words and phrases that raise many doubts and questions. Not only contemporary translators and biblical scholars contend with these difficulties, but ancient and medieval commentators did as well. The Aramaic Targums testify to the early Jewish exegesis and interpretation of Gen 49. This article presents the paraphrase and discusses a few selected verses of the Aramaic version of Torah (Tg. Onq., Tg. Neof., Frg. Tg(s)., Tg. Ps.-J.). Based on the above examples, the development of principal Jewish views on eschatology (49:1-2) and of Messianic expectations in context of Jacob’s blessing of the tribe of Judah (49:8-12) is portrayed. The last part of this article comprises the rendering and the meaning of the Targumic animal metaphors based on the examples of Issachar (49:14-15) and of Benjamin (49:27) that significantly differ from the Hebrew text.